Transformation of the Agricultural Sector in Sulawesi Island: A Panel Data Approach - Lestari Gita Nur'aini; Teguh Endaryanto; Muhammad Irfan Affandi (Institut Pertanian Bogor, 2025)
Technological revolutions, globalization, and complicated market dynamics have expedited the transformation of economic structures. This process is further influenced by the diversity of natural resources among regions, which drives economic development. In today's world, understanding economic change is critical for promoting long-term economic growth. The purpose of this study was to examine structural changes in the agriculture sector and its subsectors on Sulawesi Island, as well as the variables that affect them. The analytical approaches used include descriptive analysis of panel data processed with Microsoft Excel and panel data regression. The findings demonstrate that between 2010 and 2022, Sulawesi's agriculture industry lost 6.24% of its GDP contribution, as did all its subsectors. This decrease was complemented by a rise in the industrial sector's contribution of 5.43%. In the regression analysis, the fixed effect model (FEM) proved to be the best fit. Population density (X1) and the Indonesian democracy index (IDI) (X3) had a positive and significant influence on economic transformation, whereas farmers' terms of trade (FTT) (X4) and the number of people living in poverty (X5) had a negative and significant impact on Sulawesi's agricultural economy transformation. It is suggested that agribusiness operators vary processed products based on agricultural raw materials to aid and balance economic transition. Keywords: economic transformation, fixed effect model, panel data regression, sectoral GDP contribution, structural shift